2022
DOI: 10.1044/2021_lshss-21-00070
|View full text |Cite
|
Sign up to set email alerts
|

From a Distance: Comparison of In-Person and Virtual Assessments With Adult–Child Dyads From Linguistically Diverse Backgrounds

Abstract: Purpose: Our proof-of-concept study tested the feasibility of virtual testing using child assessments that were originally validated for in-person testing only. Method: Ten adult–child dyads were assigned to complete both in-person and virtual tests of language, cognition, and narratives. Child participants fell between the ages of 4 and 8 years; adult participants were speech-language clinicians or researchers with experience in administering child ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Further research can also provide evidence of telepractice effectiveness. Notably, few studies document evidence of telepractice effectiveness for assessment (Pratt et al., 2022). Thus, it is crucial to foster positive attitudes towards telepractice among SLTs through resource development and more evidence‐based research.…”
Section: Discussionmentioning
confidence: 99%
“…Further research can also provide evidence of telepractice effectiveness. Notably, few studies document evidence of telepractice effectiveness for assessment (Pratt et al., 2022). Thus, it is crucial to foster positive attitudes towards telepractice among SLTs through resource development and more evidence‐based research.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the COVID-19 pandemic, the MAIN was subsequently adapted for online use (Hamdani et al, 2021). The online administration of the MAIN was employed in the study by Pratt et al (2022). They noted during the data collection that participants did not always clearly see what was going on in the pictures and that the size of the pictures needed to be increased.…”
Section: Limitationsmentioning
confidence: 99%
“…Based on several studies that compared speech and language assessments online and in-person, Peña and Sutherland (2022) concluded that it is possible to reliably assess children using online procedures. Especially relevant here is the study by Pratt et al (2022) who compared online and in-person narrative comprehension using the Multilingual Assessment Instrument for Narratives (MAIN; Gagraina et al, 2019) in English and Spanish. The study indicated a high correlation between the scores reflecting comprehension of story macrostructure for online and in-person assessments.…”
Section: Introductionmentioning
confidence: 99%
“…Other concerns include ease of access. Difficulty with remote mouse control was noted by Pratt et al (2022) in their study comparing in-person and virtual assessments. Specifically, they noted that many of the younger children in their study, who ranged from 4 to 8 years of age, required adult assistance to make selections on the screen.…”
Section: How Do We Get Set Up To Conduct An Assessment Remotely?mentioning
confidence: 99%
“…For a more detailed discussion, see Kester (2020) in the ASHA LeaderLive. Pratt et al (2022) conducted a proof-ofconcept study to test the feasibility of using assessment tools that were created for inperson testing in a remote setting. They explored performance on a variety of testing tools and tasks and found a significant positive association between performance for in-person and virtual conditions.…”
Section: There Are Studies That Show Minimal Discrepancy Between Remo...mentioning
confidence: 99%